A new geography of inequality: Top incomes in Italian regions and inner areas - Demetrio Guzzardi; Salvatore Morelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
Detailed distributional estimates at finer geographical levels remain scarce, despite their critical relevance for household well being and policy intervention. This paper leverages Italian income tax records dating back to 1976 focusing on top income concentration and inequality across the country's regions, macro-areas, and the recently introduced classification of the National Strategy for Inner Areas (SNAI). Our analysis reveals a persistent rise in income concentration over the past few decades, particularly among the top earners, while also highlighting nuanced regional and sub-regional dynamics. Notably, city size plays a crucial role, with larger cities experiencing a more pronounced level of income concentration compared to smaller ones. Southern regions exhibit lower income concentration levels among the top income groups, emphasizing the need for disaggregated analyses to capture these complexities accurately.
Keywords: D31; H20; J3; R1; 330; Income Inequality; Top Income Shares; Italy; Inner Areas; Spatial Inequality; Income Tax Data; National Accounts